Laboratory evaluation of a post-fire ground treatment to mitigate soil erosion and runoff - Moden, Kayla Nicole, author; Bareither, Christopher A., advisor; Scalia, Joseph, IV, committee member; Stevens-Rumann, Camille S., committee member (Colorado State University. Libraries, 2018)
The objective of this study was to assess the efficacy of using agricultural straw mulch as a post-fire ground treatment to mitigate soil erosion and runoff. A laboratory research program was carried out to measure soil erosion and runoff in a physical slope-model experiment (surface dimensions = 76 cm long x 30 cm wide). Intact block samples were collected that represented conditions in Colorado wildfire prone areas. The vegetation on select block samples was burned to simulate a high-intensity wildfire. Unburned block samples with varying amounts of vegetation and burned block samples with varying amounts of straw mulch (0, 0.06, 0.11, and 0.22 kg/m2) were tested in the slope-model experiment at a slope of 28o under a simulated rainfall of 48 mm/h for 40 min. Burned block samples were exposed to two rainfall simulations conducted three days apart to explore changes in soil hydraulic properties due to potential soil crust formation. Runoff, and eroded sediment were collected during simulated rainfall, and intact subsamples were collected from unburned and burned block samples after the rainfall simulations to evaluate the effects of high severity burning on physical characteristics and hydraulic and mechanical properties (i.e., dry density, total organic carbon, hydraulic conductivity, water repellency, and shear strength). Burning exponentially increased erosion compared to unburned conditions and all rates of straw mulch reduced soil erosion to levels consistent with unburned samples. Runoff and erosion increased with a decrease in natural surface vegetation on unburned samples and increased with a decrease in straw mulch applied to burned samples. Notable changes in geotechnical properties with high severity burning were not found in this study, which suggested that the observed increase in erosion on bare burned samples during rainfall simulations was attributed to destruction of surface cover with burning.